Ruanjian Sanjie decoction exhibits antitumor activity by inducing cell apoptosis in breast cancer - Zhao,X; Zhao,J; Yao,Q; Zhang,G; Shen,H; Yague,E; Hu,Y (Oncology Letters, 2017)
Traditional Chinese medicine, based on theories developed and practiced for >2,000 years, is one of the most common complementary and alternative types of medicine currently used in the treatment of patients with breast cancer. Ruanjian Sanjie (RJSJ) decoction, is composed of four herbs, including Ban xia (Pinellia ternata), Xia ku cao (Prunella vulgaris), Shan ci gu (Cremastra appendiculata) and Hai zao (Sargassum pallidum), and has traditionally been used for softening hard lumps and resolving hard tissue masses. However, the active compounds and mechanisms of action of RJSJ remain unknown. The present study demonstrated the antitumor activity of RJSJ against Ehrlich ascites carcinoma in Swiss albino mice and breast cancer xenografts in nude mice. Notably, RJSJ does not induce body weight loss, immune function toxicity or myelosuppression in mice, indicating that it is safe and well tolerated. In addition, RJSJ shows potent cytotoxicity against breast cancer cells in vitro by the suppression of the antiapoptotic proteins Bcell lymphoma 2 and survivin, leading to the activation of caspase3/7 and caspase9, and the apoptotic cascade. These findings provide a clear rationale to explore the therapeutic strategy of using RJSJ alone or in combination with chemotherapeutic agents for breast cancer patients and the characterization of its active principles.